Orientacja na Prawo . pismo Warszawskiego Oddziału Liberalno-Demokratycznej Partii "Niepodległość", no. 10, 1987 (s.n.], 1987)
Creation and circulation: From vol.5, no. 64(1990) published legally. Last issue no. 1/2(February 1992)